Effect of Lactobacillus paracasei HII01 on lipid profile and blood parameters in hypercholesterolemic patients: A preliminary study - Chaiyasut, Chaiyavat; Sivamaruth, Bhagavathi Sundaram; Sirilun, Sasithorn; Tirawat, Yaowalak; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Probiotics are live microbes that when administered in suitable amounts, confer a health benefit on the host. Probiotics are considered as a complementary and supportive therapeutic agent for the treatment of several diseases and for the management of several disorders. Hypercholesterolemia is a major risk factor for the incidence of cardiovascular (CV) diseases. Several pharmacological and dietary approaches are proposed and used to improve the cholesterol profile. Aims and Objective: The objective of the current study was to study the effect of probiotic supplementation (Lactobacillus paracasei HII01) on high-density lipoprotein (HDL), and low-density lipoprotein (LDL), lipopolysaccharide (LPS), and immunoglobulin A (IgA) levels in hypercholesterolemic patients. Materials and Methods: Ten hypercholesterolemic subjects were supplemented with 12.5 × 109 CFU of HII01 per day for 12 weeks. Blood samples were collected at baseline and after the intervention period. The LDL-C, HDL-C, LPS, and IgA content were assessed by outsourcing and ELISA methods. Results: After 12 weeks of intervention, HDL (from 61.14 ± 9.65 to 67.29 ± 7.99 mg/DL), LDL (from 141.57 ± 31.95 to 126.29 ± 36.23 mg/DL), IgA (446.31 ±262.00 to 939.62 ± 758.52 ng/ml), and LPS (113.53 ± 40.07 to 72.78 ± 32.39 pg/ml) levels were significantly changed in the probiotic-supplemented group when compared to the baseline value. Conclusion: The supplementation of L. paracasei HII01 may help to improve the lipid profile, reduce the endotoxin level and have the impact of immune activation in hypercholesterolemic subjects. Additional studies are mandatory to disclose the favorable effect of the probiotic strain L. paracasei HII01.